(untitled) (Research, Society and Development, 2021)
Considering the lower prevalence of pediatric patients with COVID-19, health professionals are more familiar with interventions aimed at adults; thus, understanding the symptoms and which approaches can be useful for pediatric patients with COVID-19 is of great importance for health professionals. The study aimed to aggregate scientific data on procedures and treatments performed on pediatric patients (aged 6 to 17 years) with COVID-19. A systematic literature search was performed in five electronic databases (i.e., PubMed, CINAHL, Google Scholar, and LILACS). Literature analyses were performed in English and Chinese, between November 2019 and December 2020. For data classification, the web application Rayyan® was used. Studies have shown that in most cases, children are asymptomatic. However, when symptomatic, they present fever, cough, intestinal infection, and vomiting. It is noteworthy that the respiratory rate and stool tests were significant indicators of the disease. Regarding treatment, oxygen support is essential during the hospitalization of patients and, antiviral therapy with Lopinavir and Ritonavir has shown significant results in a few isolated cases. It is concluded that the main symptoms of SARS-CoV-2 in pediatric patients are mild symptoms similar to those of common flu. In addition, respiratory rate and examinations based on fecal samples are good indicators of the disease in children of both sexes, as well as antiviral therapies and early isolation at the beginning of the disease are significant for the healing process.